Epigallocatechin-3-gallate prior to composite resin in abfraction lesions: a split-mouth randomized clinical trial - Luísa Valente Gotardo Lara Alves; Lisiane Martins Fracasso; Thiago Vinicius Cortez; Aline Evangelista Souza-Gabriel; Silmara Aparecida Milori Corona (Restorative Dentistry & Endodontics)
ObjectivesNatural extracts have been investigated as a biomimetic strategy to mechanically strengthen the collagen network and control the biodegradation of extracellular matrix. This study evaluated the effect of epigallocatechin-3-gallate (EGCG) on abfraction lesions prior to the composite resin.Materials and MethodsThe sample consisted of 30 patients (aged between 28 and 60 years) with abfraction lesions located in 2 homologous premolars. The teeth were randomly assigned according to dentin treatment: 0.02% EGCG solution or distilled water (control). After enamel acid etching, the solutions were applied immediately for 1 minute. The teeth were restored with Universal Adhesive (3M) and Filtek Z350 XT (3M). Analyzes were done by 2 independent examiners using modified USPHS (retention, secondary caries, marginal adaptation, and postoperative sensitivity) and photographic (color, marginal pigmentation, and anatomical form) criteria at baseline (7 days) and final (18 months). The data analysis used Friedman and Wilcoxon signed-rank tests (α = 0.05).ResultsAt baseline, all restorations were evaluated as alpha for all criteria. After 18 months, restorations were evaluated as alpha for secondary caries, color, and marginal pigmentation. There was significant difference between baseline and 18 months (p = 0.009) for marginal adaptation and postoperative sensitivity (p = 0.029), but no significant difference were verified between treatments (p = 0.433). The EGCG group had a restoration retention rate of 93.3%, while the control group had 96.7%.ConclusionsThe application of EGCG solution on abfraction lesions did not significantly influence the survival of the restorations based on clinical and photographic criteria.